Nano ZnO/amine composites antimicrobial additives to acrylic paints - H.B. Kamal; M.S. Antonious; M.A. Mekewi; A.M. Badawi; A.M. Gabr; K. El Baghdady (Egyptian Journal of Petroleum)
Nano ZnO has been widely used as an antimicrobial agent not only for food packaging purposes but also in many coating processes. The present work is meant to enhance such functions through the preparation of sustainable and safe conduct of nano ZnO composites with amine derivatives that are characterized by their antimicrobial and anti-fouling functional activities. The results obtained revealed a more comprehensive approach to the antimicrobial function based on the reported active oxide species role. The oxide/amine composites and the acrylic emulsion paint were characterized chemically and structurally through FT-IR, TGA and TEM supported by biological assessment of each ZnO/amine composite action. Results of the study concluded that equilibrium between the nano ZnO particles size, their dispersion form, and amine ability to stabilize the actively produced oxygen species responsible for the antimicrobial function, should all be accounted for when persistence of antimicrobial agent efficiency is regarded.